Simulation of Hip Prosthesis based on Dynamic Loading using Finite Element Method - Tajul Ariffin, Muhammad Firdaus; abdullah, haslina (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Hip prosthesis is important in the surgical industry, and research on hip prostheses is crucial to providing the best surgeries for patients. This study aims to design hip prosthesis and analyze the stress distribution and displacement occurring on hip prostheses based on different types of designs under dynamic loading. The outcome of this study is to identify the best design of hip prosthesis to implement for patients. The method of analysis involves using SolidWorks software for designing the hip prosthesis and Abaqus software for simulation in the Finite Element Method (FEM). Three design of hip prosthesis has been designed to assessed the effect of the geometry shape on the stress distribution. Based on the analysis, it was found the lowest readings of stress distribution and displacement on the hip prosthesis, as these are the optimal characteristics for the best hip prosthesis. Results from the analysis show that Design 3 has the lowest readings of stress distribution and displacement, making this design suitable for implementation in patients.